Functional and Regulatory Characterization of Three AMTs in Maize Roots - Hao, Dong-Li; Zhou, Jin-Yan; Yang, Shun-Ying; Huang, Ya-Nan; Su, Yan-Hua (Frontiers in Plant Science, 2020)
Maize grows in nitrate-dominated dryland soils, but shortly upon localized dressing of nitrogen fertilizers, ammonium is retained as a noticeable form of nitrogen source available to roots. Thus in addition to nitrate, the absorption of ammonium can be an important strategy that promotes rapid plant growth at strong nitrogen demanding stages. The present study reports the functional characterization of three root-expressed ammonium transporters (AMTs), aiming at finding out functional and regulatory properties that correlate with efficient nitrogen acquisition of maize. Using a stable electrophysiological recording method we previously established in Xenopus laevis oocytes that integrates the capture of currents in response to voltage ramps with onsite stability controls, we demonstrate that all three ZmAMT1s engage NH4+ uniporting as ammonium uptake mechanisms. The Km value for ZmAMT1.1a, 1.1b or ZmAMT1.3 is respectively 9.9 μM, 15.6 μM or 18.6 μM, indicating a typical high-affinity transport of NH4+ ions. Importantly, the uptake currents of these ZmAMT1s are markedly amplified upon extracellular acidification. A pH drop from 7.4 to 5.4 results in a 140.8%, 64.1% or a 120.7% increase of ammonium uptake activity through ZmAMT1.1a, 1.1b or ZmAMT1.3. Since ammonium uptake by plant roots accompanies a spontaneous acidification to the root medium, the functional promotion of ZmAMT1.1a, 1.1b and ZmAMT1.3 by low pH is in line with the facilitated ammonium uptake activity in maize roots. Furthermore, the expression of the three ZmAMT1 genes is induced under ammonium-dominated conditions. Thus we describe a facilitated ammonium uptake strategy in maize roots by functional and expression regulations of ZmAMT1 transporters that may coordinate with efficient acquisition of this form of nitrogen source when available.